FTIR measurement of monomer fractions in dilute alcohol-acetone systems for the evaluation of the sPC-SAFT EoS - Kruger, Francois Johan (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScEng)-- Stellenbosch University, 2013.